Cenário acadêmico institucional dos cursos de Arquivologia, Biblioteconomia e Museologia do Brasil - Gabrielle Francinne de Souza Carvalho (2013)
The Archival Science, Library Science and Museology are scientific fields that have got different training trajectories and academic-institutional settings. Thus, we started with the assumption that these fields, permeated by power relations, can be influenced by theplace where each course is located, as well as the fact that they could be near and / or far from each other and also from the Information Science post-graduation course. The objective was to analyze the academic-institutional influence on Archival Science, Library Science and Museology in Brazil. Therefore, the teaching class planning of specific theoretical subjects and a questionnaire with five open questions that was sent to these teachers were used as an instrument for data collection. It was also identified the degree of each teacher in order to analyze the influence of their training choices in the references cited in their class planning. At first, we carried out the analysis of these educational plans through bibliometric method of citation analysis,after the questionnaire was analyzed using the Content Analysis Method to categorize the responses and then the Discourse Analysis Method to interpret the speeches in their contexts. It was necessary for the research to group the courses into six categories, which correspond to the proximity among them on the same education institution.Reading Bourdieu and Foucault supported the interpretation of the teaching class planning and questionnaire. References were tabulated in order to get the most cited authors, the works and also the profile of these works by type, age and language referenced in the teaching plans and the questionnaire. The results of this research showed that prevails in the disciplines the cited books, dating from the 2000s and inPortuguese. The influence of the academic-institutional analysis comes from the references and it can be seen as belonging to all six categories courses. As for the other questions in the questionnaire, it was found that teachers considered their academic formation as the most influenced factor in their choices, followed by the proximity of the post-graduate courses and lastly, the academic-institutional linking and proximityamong the undergraduate courses. Concerning Archival Science, Library Science and Museology it was possible to notice that most teachers have found links among these fields.